Psychological Status and Influencing Factors of Hospital Medical Staff During the COVID-19 Outbreak - Yao, Yang; Tian, Yao; Zhou, Jing; Diao, Xin; Cao, Bogan; Pan, Shuang; Di, Ligai; Liu, Yan; Chen, Hui; Xie, Chunxia; Yang, Yuanli; Li, Feiyu; et al. (Frontiers in Psychology, 2020)
Background: The aim of this study was to analyze the psychological status of and its influencing factors of health care workers (HCWs). to provide sufficient theory and scientific basis for the formulation and implementation of relevant policies and measures in improving the psychological status of HCWs. Method: 1002 members of the HCWs from Xi’an and Wuhan were recruited and surveyed by using a self-administered questionnaire and 12-item General Health Questionnaire (GHQ-12) from Feb 1 to Feb 20, 2020. GHQ-12 scale was divided by 3 points. The score greater than 3 divided into the positive group. All date was analysis by SPSS. Results: More than half of the participants (61.1%) reported psychological distress. The HCWs have sufficient information about the COVID-19 symptoms, prognosis, treatment, infection route and preventive measures (medians ranged from 6/9 to 8/9). Female, engaged in clinic work less than 7 years, married person and working in Wuhan were risk factors affecting the psychological status of HCWs (P＜0.05). Conclusion: Psychological distress is common in HCWs during COVID-19 outbreak. Hospitals and relevant departments should provide psychological support to HCWs and provide them with sufficient information they needed.